La valoración del inventario de mercadería como herramienta para el mejoramiento de la gestión financiera - Guamán Yanza, Tatiana Maribel (2015)
This inclusive labor is developed in the company ZACHER Y COMPAÑÍA, in order to know if you are valuing their inventories so that indicates the International Accounting Standard IAS 2, in relation to the deterioration; in order to verify if reflected in the financial statements are reliable values. Among the techniques and instruments applied it was: observation and interviews addressed to the general manager; a qualitative methodology, bibliographical research exploratory and descriptive type was used. It should be emphasized that the company has a large stock of goods for sale, this resulted in a lack of control in their inventories, causing problems with the detection and control of damaged merchandise and therefore the information in the financial statements was not correct, this allowed the enforcement IAS 2 on inventories in order to determine impairment; the design of policies and internal control procedures in the area of inventories in relation to its deterioration, the same as with its implementation will improve the work and function of the inventories of the company; this will have management reports, physical inventory with real data and proof of damaged materials.